(untitled) (Maʿālim al-Qurʾān wa al-Sunnah, 2020)
This research aims to identify the factor in the emergence of esoteric spirituality in the West and its export to the Islamic world, as currents have appeared in the West that promote this doctrine- competing with the religious proposition, offering non-religious alternatives in order to achieve the same goals and objectives of religiosity, working to change the person from within, instead of through the mediation of the prophets and the limitations of revelation. The descriptive analytical and critical approach is used in this research, for the most important results of this research, the contemporary esoteric spirituality is a doctrinal doctrine that has been fabricated in the West by reviving ancient mystical and pagan beliefs and ideas such as Hinduism, Buddhism and Taoism, and the interpretation of sacred texts by the People of the Book in a spiritual interpretation that is similar to the Jewish Kabbalah, Christian Gnosticism and some mystical and mystical ideas in the Islamic world, and because the dominant culture has authority over others. Correspondingly, these ideas have appeared in the Islamic world, and someone has interpreted the texts of the Noble Qur’an to coincide with these deviant ideas.